2007
DOI: 10.1158/0008-5472.can-06-3831
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Endothelial Growth Factor Receptor-1 Expression by Specificity Proteins 1, 3, and 4 in Pancreatic Cancer Cells

Abstract: Vascular endothelial growth factor receptor-1 (VEGFR1) is expressed in cancer cell lines and tumors and, in pancreatic and colon cancer cells, activation of VEGFR1 is linked to increased tumor migration and invasiveness. Tolfenamic acid, a nonsteroidal anti-inflammatory drug, decreases Sp protein expression in Panc-1 and L3.6pl pancreatic cancer cells, and this was accompanied by decreased VEGFR1 protein and mRNA and decreased luciferase activity on cells transfected with constructs (pVEGFR1) containing VEGFR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
143
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(164 citation statements)
references
References 46 publications
20
143
1
Order By: Relevance
“…adenocarcinoma and was associated with advanced stage and poor survival. Aberrant Sp1 overexpression was also found in cell lines derived from pancreatic cancers (22,23). Our study, for the first time, has described the expression of Sp1 in patients with pancreatic adenocarcinoma and showed the association of Sp1 with advanced stage and poor survival.…”
Section: Discussionsupporting
confidence: 63%
“…adenocarcinoma and was associated with advanced stage and poor survival. Aberrant Sp1 overexpression was also found in cell lines derived from pancreatic cancers (22,23). Our study, for the first time, has described the expression of Sp1 in patients with pancreatic adenocarcinoma and showed the association of Sp1 with advanced stage and poor survival.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, knockdown of Sp1 in pancreatic cancer cells decreases growth and invasion and induces apoptosis, confirming the pro-oncogenic functions of this factor (49). These results suggest that drugs such as metformin and other agents (31)(32)(33)(34)(35)(36)39) that target Sp1, Sp3, and Sp4 represent a class of new mechanism-based drugs that can be used in combination therapies for treating this deadly disease.…”
Section: Discussionsupporting
confidence: 52%
“…This involved down-regulation of specificity protein (Sp) transcription factors Sp1, Sp3, and Sp4 and pro-oncogenic Sp-regulated genes such as bcl2, fatty acid synthase (FAS), survivin, vascular endothelial growth factor (VEGF), and VEGF receptor 1 (VEGFR1) (31). The anticancer activities of metformin are also similar to * This work was supported, in whole or in part, by National Institutes of Health that observed after knockdown of Sp1 or all three Sp proteins by RNA interference in cancer cells, and this includes growth inhibition, induction of apoptosis, reversal of epithelial to mesenchymal transition, and decreased migration/invasion (32)(33)(34)(35)(36). Metformin also inhibits NFB and decreases cyclin D1 and ErbB2 in cancer cell lines (13,20,27,28), and these gene products are also decreased after Sp1, Sp3, and Sp4 silencing by RNAi or by other drugs that down-regulate Sp proteins (32)(33)(34)(35)(36).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Although Sp1 is widely expressed in tumors, there is increasing evidence that Sp3 and Sp4 are also expressed in cancer cells and contribute to Sp-dependent procarcinogenic responses (20)(21)(22)(23)(24)(25). Using RNA interference, it was shown that Sp1 knockdown using a small inhibitory RNA for Sp1 (iSp1) inhibited G 0 -G 1 to S phase progression in MCF-7 breast cancer cells (25).…”
Section: Introductionmentioning
confidence: 99%